Effect of levels of metabolizable energy and protein on the zootechnical performance of laying quails (2014)
This study, carried out in the University of the Llanos, aimed to determine the optimal level of metabolizable energy and protein quail (Coturnix japonica) in laying phase. We used 480 quails 10 weeks old and 94±10 g of initial weight, distributed in a completely randomized experimental design, 4x4 factorial arrangement, with four levels of metabolizable energy (2750, 2850, 2950 and 3050 kcal EM.kg1), and four levels of crude protein (17.5, 19.0, 20.5 and 22.0%), with three replicates and 10 birds. The trial lasted 24 weeks, during which water and food were supplied at will. The results were processed in the SAEG program (2007), subjected to analysis of variance and polynomial regression. The results showed no interaction between the levels of metabolizable energy and protein, which means the factors acted independently. Analyzing each factor, a quadratic influence (p <0.05) was observed on egg production. The egg production was increased (91%) to the level of 2750 kcal of EM.kg1 and 20.5% crude protein. These levels provided a feed conversion related dozen eggs/kg was of 0.338, the value of egg mass of 2.852 with 3050 kcal EM.kg-1 and 19% crude protein. The equations y = -0.0038x2 + 0.1456x - 0.5771, y = R2 = 75.7 -8E-05x2 + 0.4466x-533.05, R2 = 0.89, allow to estimate the requirements of crude protein (2791 kcal EM.kg-1) and metabolizable energy (19.16%) for egg production.